The role of stroke rate and intensity on rowing technique - Ettema, G.; Haug, A.; Ludvigsen, T. P.; Danielsen, J. (Sports Biomechanics, 2022)
We investigated the notion that ergometer rowing technique at different intensities, but self-chosen stroke rates (SR) would resemble each other more than when rowing at other intensity-SR combinations. Twelve competitive male rowers performed ergometer rowing at three intensities x three SR, including the self-chosen one. Kinetics were recorded and inverse dynamics applied to estimate joint powers. Our results indicate strong effects of intensity and SR on most kinetic variables (e.g., drive length, time and velocity, recovery time, work per stroke). These effects were hardly reduced when only considering the preferred SR-intensity combinations, except for time profiles of elbow, shoulder, and hip joint powers. SR was mostly regulated by adapting recovery time, leaving drive time and its kinetics mostly affected by intensity. SR and intensity had marginal effects on relative joint power. Kinetics of drive only are largely independent of intensity and SR instruction. Still, this kinetic resemblance is strongest at preferred SR. We conclude that, given a fixed resistance, work rate is mostly steered through SR: Work per stroke is `set` for the given power requirement. A necessary additional large adjustment in stroke rate is done mostly by modifying recovery time.